Staying Quit After Release (SQuARe) trial protocol: a randomised controlled trial of a multicomponent intervention to maintain smoking abstinence after release from smoke-free prisons in Victoria, Australia. Issue 6 (4th June 2019) - Young, Jesse T; Puljević, Cheneal; Love, Alexander D; Janca, Emilia K; Segan, Catherine J; Baird, Donita; Whiffen, Rachel; Pappos, Stan; Bell, Emma; Kinner, Stuart A
Abstract : Introduction: Smoke-free policies have been introduced in prisons internationally. However, high rates of relapse to smoking after release from prison indicate that these policies typically result in short-term smoking cessation only. These high rates of relapse, combined with a lack of investment in relapse prevention, highlight a missed opportunity to improve the health of a population who smoke tobacco at two to six times the rate of the general population. This paper describes the rationale and design of a randomised controlled trial, testing the effectiveness of a caseworker-delivered intervention promoting smoking cessation among former smokers released from smoke-free prisons in Victoria, Australia. Methods and analysis: The multicomponent, brief intervention consists of behavioural counselling, provision of nicotine spray and referral to Quitline and primary care to promote use of government-subsidised smoking cessation pharmacotherapy. The intervention is embedded in routine service delivery and is administered at three time points: one prerelease and two postrelease from prison. Control group participants will receive usual care. Smoking abstinence will be assessed at 1 and 3 months postrelease, and confirmed with carbon monoxide breath testing. Linkage of participant records to survey and routinely collected administrative data will provide further information on postrelease use of health services and prescribed medication. Ethics and dissemination: Ethical approval has been obtained from the Corrections Victoria Research Committee, the Victorian Department of Justice Human Research Ethics Committee, the Department of Human Services External Request Evaluation Committee and the University of Melbourne Human Research Ethics Committee. Results will be submitted to major international health-focused journals. In case of success, findings will assist policymakers to implement urgently needed interventions promoting the maintenance of prison-initiated smoking abstinence after release, to reduce the health disparities experienced by this marginalised population. Trial registration number: ACTRN12618000072213; Pre-results.